Level of selected nutrients in meat, liver, tallow and bone marrow from semi-domesticated reindeer (Rangifer t. tarandus L.) - Hassan, Ammar E. Ali; Sandanger, Torkjel Manning; Brustad, Magritt (International Journal of Circumpolar Health, 2012)
Objectives: To acquire new knowledge on the nutritional composition of semi-domesticated reindeer (Rangifer t. tarandus L.) and their nutritional value for humans. The results could be useful in updating the Norwegian Food Composition Database, whose current data on reindeer is limited. Study design: Cross-sectional study on population of semi-domesticated reindeer from 2 northern Norwegian counties (Finnmark and Nordland). Methods: Semi-domesticated reindeer carcasses (n 31) were randomly selected, from which meat, liver, tallow and bone marrow samples were collected. Selected vitamins, minerals, fatty acids and total lipids were studied. Results: As expected, reindeer meat was found to be lean (2% total lipid), thus it is a good source of low-fat meat. The meat was also found to be a good source of vitamin B12, docosapentaenoic acid (C22:5 n-3) and a-linolenic acid (C18:3 n-3). Statistically significant differences (pB0.05) in most of the nutrient levels between meat and the rest of the studied reindeer tissues were observed. In most cases, the liver, tallow and bone marrow had higher nutritional values when compared to meat. Liver had the highest concentrations of vitamin A, all vitamin B types, vitamin C, iron, selenium and the total amount of polyunsaturated fatty acids (n-3). Additionally, liver was the only edible tissue that contained vita-mins B9 and C. The vast majority of the vitamin concentrations in liver, tallow and bone marrow were significantly correlated with the concentrations in meat (pB0.05). Conclusions: The studied tissues from reindeer demonstrated that reindeer is a valuable food source that could meet or contribute to the consumers’ nutritional recommended daily allowance (RDA).